(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
A significant number of scientific articles about polycystic ovary syndrome (PCOS) are being published globally. Publications on PCOS from Bangladesh cover various disciplines and types, including review articles and case reports. A narrative review of the published original articles on Bangladeshi women with PCOS was released in January 2023. In this review, we included only original articles published since 2023. Additionally, some articles missing from the previous review, especially those related to intervention studies, were incorporated. We summarized the original articles’ findings narratively. [J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 45-59]